Role of BOEY score in association with age in predicting mortality and morbidity in peptic perforation - Tudu, Paran; Roy, Pritish; Naskar, Partha Sarathi (International Surgery Journal, 2022)
Background: Peptic perforation generally requires immediate surgery. BOEY scoring system is a simple way to predict the mortality and morbidity in peptic perforation. Apart from the factors mentioned in BOYE score, patient’s age is also important. The study evaluates the accuracy of BOEY scoring system in predicting post-operative morbidity and mortality in patients operated for peptic perforation as well as inclusion of age as one of the criteria for the scoring system and thus modifying the system. Methods: Total 103 patients were taken for this institution based prospective observational study. The 18th months study was planned as follow - initial 14 months for patient study, next 2 months for compilation of data, further 2 months for computation of statistics and final construction. Results: Patients with BOYE score 0, 1, 2, 3 has morbidity rates as follow 7.01,19.29, 36.85 and 36.85 respectively. Whereas mortality rate was 0, 0, 9.09 and 90.91 respectively. 76.4% of patients with post-operative complications belonged to age > 45 years. All the cases of mortality were >45 years of age. Conclusions: It is simple and can assist in risk stratification of patients with perforated peptic ulcer. It can help us to identify high-risk patients preoperatively and help in better use of limited facilities. And lastly, a modification can be done by including age (> 45 years) with the other three parameters of the BOEY scoring system.